2021
DOI: 10.1186/s40694-021-00118-3
|View full text |Cite
|
Sign up to set email alerts
|

State of the art, recent advances, and challenges in the field of fungal mycelium materials: a snapshot of the 2021 Mini Meeting

Abstract: Material development based on fungal mycelium is a fast-rising field of study as researchers, industry, and society actively search for new sustainable materials to address contemporary material challenges. The compelling potential of fungal mycelium materials is currently being explored in relation to various applications, including construction, packaging, “meatless” meat, and leather-like textiles. Here, we highlight the discussions and outcomes from a recent 1-day conference on the topic of fungal mycelium… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 11 publications
0
9
0
Order By: Relevance
“…Mycelium bio-composites are a new kind of material, which have gained increasing interest in the last decade. 7 These materials are based on a cellulose-or lignocellulose-rich substrate colonized by fungal mycelium and, as such, represent an upcycled agricultural residue. Their production is considered to be environmentally friendly since it relies entirely on circular biological processes, and the final product is biodegradable.…”
Section: ■ Introductionmentioning
confidence: 91%
“…Mycelium bio-composites are a new kind of material, which have gained increasing interest in the last decade. 7 These materials are based on a cellulose-or lignocellulose-rich substrate colonized by fungal mycelium and, as such, represent an upcycled agricultural residue. Their production is considered to be environmentally friendly since it relies entirely on circular biological processes, and the final product is biodegradable.…”
Section: ■ Introductionmentioning
confidence: 91%
“…A thorough framework of the main parameters influencing mycelium-based composites was presented in various studies recently and identified advantageous material properties, such as low thermal conductivity, high acoustic absorption, and fire protection properties [ 10 , 11 , 12 ]. However, challenges generally arise from research knowledge gaps [ 14 ] that limit the use of these materials only to non-structural or semi-structural applications.…”
Section: State Of the Artmentioning
confidence: 99%
“…These and other major issues that need to be discussed within the community (e.g. on how to standardize manufacturing processes and, thus, material properties or how to integrate life cycle assessments to determine environmental footprints) have been summarized by Attias et al [ 14 ]. They refer in their meeting report to the first international meeting dedicated fully to fungal-based materials.…”
Section: Main Textmentioning
confidence: 99%
“…They refer in their meeting report to the first international meeting dedicated fully to fungal-based materials. This “Fungal Mycelium Materials Mini Meeting” was held remotely in August 2021 and brought together delegates from ten European research institutions with scientific backgrounds in materials science, fungal bio(techno)logy, engineering, art, and architecture [ 14 ]. This diversity in educational backgrounds was and is an opportunity and a challenge at the same time.…”
Section: Main Textmentioning
confidence: 99%